2020
DOI: 10.31223/osf.io/qc9jh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The perpetual fragility of creeping hillslopes

Abstract: Soil-mantled hillslopes owe their smooth, convex shape to creep; the slow and persistent, gravity-driven motion of grains on slopes below the angle of repose. Existing models presume that soil creep occurs via mechanical displacement of grains by (bio)physical disturbances. Recent simulations, however, suggest that soil can creep without these disturbances, due to internal relaxation dynamics characteristic of disordered and fragile solids such as glass. Here we report experimental observations of creeping mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
(94 reference statements)
0
11
0
Order By: Relevance
“…In essence, µ(I ) is very similar to fluid rheology, but allows for the role of changing confining pressure with depth. However, the extremely low solifluction velocities observed in the field indicate that solifluction occurs not as a granular flow but well within the granular creep regime (63) that has been shown to describe soil transport velocities on temperate hillslopes (64,65). Granular creep rheology is still at the forefront of granular physics research.…”
Section: Discussionmentioning
confidence: 99%
“…In essence, µ(I ) is very similar to fluid rheology, but allows for the role of changing confining pressure with depth. However, the extremely low solifluction velocities observed in the field indicate that solifluction occurs not as a granular flow but well within the granular creep regime (63) that has been shown to describe soil transport velocities on temperate hillslopes (64,65). Granular creep rheology is still at the forefront of granular physics research.…”
Section: Discussionmentioning
confidence: 99%
“…( 8), particle size is a factor in the transport coefficient because it controls the mean free path of particles in a soil creeping by dilational processes [Furbish et al, 2009]. Although field data from Neeley et al [2019] suggest that coarser soils have a higher transport coefficient, laboratory experiments have demonstrated that, for the same input of energy, coarse-grained soils will creep faster than fine-grained soils [Supplement to Deshpande et al, 2020]. In addition, of the various factors that could affect the rate of soil creep, particle size is the one with the most potential to vary by multiple orders-of-magnitude between watersheds eroding at different rates [Marshall and Sklar, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Herein we focus on rarefied motions of particles which, once entrained, travel downslope over the land surface. This notably includes the dry ravel of particles down hillslopes following disturbances (Roering and Gerber, 2005;Doane, 2018;Doane et al, 2019;Roth et al, 2020) or upon their release from obstacles (e.g., vegetation) following failure of the obstacles (Lamb et al, 2011(Lamb et al, , 2013DiBiase and Lamb, 2013;DiBiase et al, 2017;Doane et al, 2018Doane et al, , 2019, and the motions of rockfall material over the surfaces of talus and scree slopes (Gerber and Scheidegger, 1974;Kirkby and Statham, 1975;Statham, 1976;Dorren, 2003;Luckman, 2013) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%